2014
DOI: 10.18632/oncotarget.2589
|View full text |Cite
|
Sign up to set email alerts
|

Elevated endoplasmic reticulum stress reinforced immunosuppression in the tumor microenvironmentviamyeloid-derived suppressor cells

Abstract: The role of endoplasmic reticulum (ER) stress in cancer has been studied in detail, and ER stress is known to increase tumor cell apoptosis, and thus, reduce tumor growth. However, in our study, persistent ER stress induced by multiple administrations of low-dose thapsigargin (Tg) accelerated tumor growth in mice. Tg-mediated ER stress increased the generation of Ly6G+CD11b+ myeloid cells, but did not alter anti-tumor effector T cells. 4-Phenylbutyric acid (4-PBA), a chemical chaperone widely used as an ER str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 50 publications
2
77
0
Order By: Relevance
“…In these trials, 4-PBA inhibited growth and induced apoptosis in cancer cells from gastric, colon, and prostate cancers . This is consistent with recent findings were 4-PBA inhibited thapsigargin accelerated tumor growth, immunosuppression, and myeloid derived suppressor cell expansion (Lee et al, 2014).…”
Section: The Effect Of 4-pba In Cancer and Experimental Models Of Cancersupporting
confidence: 93%
“…In these trials, 4-PBA inhibited growth and induced apoptosis in cancer cells from gastric, colon, and prostate cancers . This is consistent with recent findings were 4-PBA inhibited thapsigargin accelerated tumor growth, immunosuppression, and myeloid derived suppressor cell expansion (Lee et al, 2014).…”
Section: The Effect Of 4-pba In Cancer and Experimental Models Of Cancersupporting
confidence: 93%
“…Our group revealed that LFA-1-expressing C26 cells interact with LSECs via ICAM-1, and that this interaction was the initial angiogenic stimulus during the early stage of liver metastasis, promoting tumor release of vascular endothelial growth factor (VEGF) (27,32), and driving the directional migration of LSECs and HSC recruitment to tumor areas (97). To further amplify this reaction, tumor cells, tumor-associated macrophages (TAMs) and myeloid-derived suppressor cells (MDSCs) contribute to VEGF secretion in response to their stimulation by TNF-α, IL-6 and NO, which are released through ICAM-1-mediated signaling pathways in KCs and LSECs (106,107). Wang and Doerschuk reported that upon ICAM-1 ligand binding, pulmonary endothelial cells undergo cytoskeletal reorganization (108), a process required for the formation of new vessels, which may also occur in the liver when interacting with ICAM-1 ligands expressed on tumor cells.…”
Section: Tumor Cell Extravasation: Opening the Liver's Doors To Invadmentioning
confidence: 99%
“…On the other hand, CD4 + T lymphocytes also contribute to immune defense against cancer development (120). However, among the immune cell populations recruited from the circulation, MDSCs are able to suppress T cell cytotoxic activity towards the tumor and promote immune suppression (106). In this context, TAMs and MDSCs also contribute to tumor progression by decreasing anti-tumor immunity and generating a pro-tumor microenvironment (106,(121)(122)(123)(124).…”
Section: Tumor Cell Extravasation: Opening the Liver's Doors To Invadmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, hypoxia results in increased HIF-1a expression through decreased degradation and increased translation (169), which upregulated iNOS and Arg1 (27,81). Endoplasmic reticulum stress has also been shown to upregulate iNOS and Arg1, as well as the ROS producing enzyme NADPH oxidase (82). The factors involved in driving MDSC expansion and/or differentiation during viral infections, including cytokines and chemokines, remain less clear.…”
Section: Factors Involved In Mdsc Expansionmentioning
confidence: 99%